Original paperRESTING PLASMA AgRP LEVELS RESPONSE TO EXERCISE-CONJUGATED DIET AND ONLY DIET IN OVERWEIGHT AND OBESE SEDENTARY FEMALES - Delphan, M.; Rashidlamir, A.; Delphan, F. (Biology of Sport, 2012)
Agouti-related peptide (AgRP) is an orexigenic neuropeptide produced mainly in the arcuate nucleus (ARC) of the hypothalamus, which leads to positive energy balance. The purpose of the present study was to investigate the resting plasma AgRP levels’ response to exercise-conjugated diet and only diet in overweight and obese sedentary female college students. Thirty subjects were randomly divided into two experimental groups and one control group. Experimental group 1 experienced 12 days of researchers’ proposed diet (D), experimental group 2 experienced 12 days of researchers’ proposed diet (every day) with 12-day running training (the intensity was 60 to 70% heart rate maximum for 50 minutes) every other day (AED) and the control group remained sedentary with a normal diet in this period. Blood samples were collected 24 hours before and after the enforced protocol. Body fat percentage (BF%) of subjects was measured using the 3-point method. Plasma AgRP levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. The data were analysed by Leven, Kolmogorov-Smirnov, one-way analysis of variance (ANOVA) and Tukey post-hoc test. At the end of the protocols, the resting plasma AgRP in the D group increased significantly (p<0.05) and in the AED group no change was observed (P>0.05). Body weight and BMI were significantly reduced for both experimental groups (P<0.001). Body fat percentage in the AED group was decreased (p<0.001) and no change was observed in the D group. The present results indicate that the AED is better than the D protocol because it leads to stability of AgRP, which may prevent lipogenesis and ultimately reduce body fat percentage.